BDNF epigenetic modifications associated with schizophrenia-like phenotype induced by prenatal stress in mice - Dong, Erbo (Biol Psychiatry, 2014)
BACKGROUND: Prenatal stress is considered a risk factor for several neurodevelopmental disorders including schizophrenia (SZ). An animal model involving restraint stress of pregnant mice suggests that prenatal stress (PRS) induces epigenetic changes in specific GABAergic and glutamatergic genes likely to be implicated in SZ including the gene for brain derived neurotrophic factor (BDNF). METHODS: Studying adult offspring of pregnant mice subjected to PRS, we explored the long-term effect of PRS on behavior and on the expression of key chromatin remodeling factors including DNA methyltransferase 1 (DNMT1), ten-eleven translocation hydroxylases (TETs), methyl CpG binding protein 2 (MeCP2), histone deacetylases (HDACs), histone methyltransferases (MLL1, SETD1, G9A and EZH1) and demethylase (LSD1) in the frontal cortex (FC) and hippocampus (HP). We also measured the expression of BDNF. RESULTS: Adult PRS offspring demonstrate behavioral abnormalities suggestive of SZ and molecular changes similar to SZ postmortem brain: a significant increase in DNMT1 and TET1 in the FC and HP but not in cerebellum, no changes in HDACs, histone methytransferases/demethylases or MeCP2, and a significant decrease in BDNF variants measured in the FC and HP. The decrease of the corresponding BDNF transcript level was paralleled by an enrichment of 5-methylcytosine and 5-hydroxylmethylcytosine levels at Bdnf gene regulatory regions. In addition, the expression of BDNF transcripts (IV and IX) was positively correlated with social approach in both PRS and non-stressed mice. CONCLUSIONS: Since patients with psychosis and PRS mice show similar epigenetic signature, PRS offspring may be a suitable model for understanding the behavioral and molecular epigenetic changes observed in SZ patients.